KOMPETENCJA MEDIALNA UCZNIÓW I NAUCZYCIELI JĘZYKÓW OBCYCH JAKO CZYNNIK WPŁYWAJĄCY NA POZIOM ICH KOMPETENCJI INTERKULTUROWEJ - Chudak, Sebastian (Neofilolog, 2019)
Intercultural competence is an expected outcome in language learning and teaching in our contemporary world. However, studies show foreign language teachers are not always aware of the importance of this goal for many reasons, the most important of which seems to be the low level of their own intercultural competence. The aim of this article is to discuss the possibilities of increasing the intercultural competence of foreign language teachers and students. The correlation between media literacy and the development of intercultural competence is discussed.